1986
DOI: 10.1177/001872088602800509
|View full text |Cite
|
Sign up to set email alerts
|

Task Complexity in Visual Inspection

Abstract: Three types of inspection complexity were tested on an inspection task using both industrial and student subjects. Items inspected varied with regard to the number of different fault types (two, four, or six), whether the inspecting standards for each fault type were the same or different, and whether faults occurred anywhere on the item or only on specific sub-areas. Number of fault types had a large effect on the search component of the task. The effect of same or different standards was largely confined to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 26 publications
3
56
1
Order By: Relevance
“…Namely, inspection performance for cases wherein defects are distributed across an entire item (e.g., aircraft fuselage) does not appear to differ from cases in which defects are confined to only part of an item (Gallwey & Drury, 1986).…”
Section: Defect Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, inspection performance for cases wherein defects are distributed across an entire item (e.g., aircraft fuselage) does not appear to differ from cases in which defects are confined to only part of an item (Gallwey & Drury, 1986).…”
Section: Defect Locationmentioning
confidence: 99%
“…However, the standards themselves must be simple and easy to interpret. Gallwey and Drury (1986) showed that inspection performance was worse when different standards had to be used for different areas of the product as opposed to the condition in which the same standards for acceptance/rejection could be applied to any defect. In addition, a computer simulation task of a real-world contact lens inspection task revealed that search times, stopping times, mean inspection time, and decision-making performance per lens all worsened as defect standard complexity increased (Rao, Bowling, Khasawneh, Gramopadhye, & Melloy, 2006).…”
Section: Standards For Comparisonmentioning
confidence: 99%
“…Eight graduate students (all enrolled in the College of Engineering at North Carolina A&T State University), between the ages of 21 to 32 years old with an average of 26 years, were recruited as subjects. Gallwey and Drury (1986) have shown that minimal differences exist between inspectors and student subjects on simulated tasks. The subjects were screened for 20/20 vision (correction if necessary) and were not paid for their time.…”
Section: Pilot Studymentioning
confidence: 99%
“…This is not the case in bridge inspections. Gallwey and Drury (1986) performed a study investigating the effect of the number of distinct defect types that the inspector must consider during an inspection. They agreed with the conclusion of Megaw (1979) that, as the number of potential defects increases, the reliability of the inspection decreases.…”
Section: Problems With Visual Inspectionsmentioning
confidence: 99%